Integration of Linux Containers in OpenStack: An Introspection - Ashish Lingayat; Ranjana R. Badre; Anil Kumar Gupta (Institute of Advanced Engineering and Science, 2018)
In cloud computing, sharing of resources is supported using heavy weighted traditional virtualization techniques. Such techniques involve hypervisors to emulate hardware for creating virtual machines. The inclusion of an additional layer of hypervisor over host operating system depreciates the performance of the virtual machine. Recent evolution is a lightweight alternative to the virtual machine called containers which have gainedpopularity among developers and administrators. Container Based virtualization has proven very efficient regarding performance, and many industries are now migrating their virtualized environment to run on Linux containers. Containers use host operating systems kernel and isolate each container by encapsulating them with their required services and packages. Linux kernel is very beneficial in implementing containers, which is the reason for the existence of Linux containers. Linux containers utilize less storage space and consume optimal computational power, giving a hike in performance. Having them integrated into the cloud surely benefits consumer and cloud provider. Many projects have extended their support in incorporating containers in the cloud. In this paper, we will discuss various Linux containers and their management tools along with cloud computing software, OpenStack, including projects undertaken by OpenStack for integrating containers in the cloud.